Risk factors and clinical consequences of side branch occlusion in left anterior descending bifurcation percutaneous coronary intervention: a validation study of the V-RESOLVE score - Wu, Xi; Wu, Mingxing; Huang, Haobo; Liu, Zhe; Huang, He; Wang, Lei (Frontiers in Cardiovascular Medicine, 2025)
Background/purposeSide branch occlusion (SBO) remains a prevalent and clinically significant complication during percutaneous coronary intervention (PCI) for bifurcation lesions, particularly those involving the left anterior descending (LAD) artery. This retrospective study aimed to assess the incidence, identify independent predictors, and evaluate the clinical consequences of SBO in the context of LAD bifurcation PCI.MethodsWe conducted a retrospective analysis of 553 patients who underwent PCI targeting LAD bifurcation lesions between 2018 and 2023. Comprehensive data encompassing clinical characteristics, angiographic findings, and procedural details were collected. The primary outcome was the occurrence of SBO, defined as a reduction in side branch TIMI flow following stent implantation. Multivariate logistic regression was applied to determine independent risk factors.ResultsSBO occurred in 41 cases (7.4%). Multivariate analysis identified true bifurcation lesions (OR 1.221, P < 0.001), an increased main vessel to side branch (MV/SB) diameter ratio (OR 1.431, P < 0.001), and higher Visual estimation-based Risk prEdiction of Side branch OccLusion in coronary bifurcation interVEntion (V-RESOLVE) scores (OR 3.736, P = 0.001) as significant independent predictors. Patients with SBO showed reduced procedural success rates (82.9% vs. 94.7%, P = 0.007), a higher incidence of periprocedural myocardial infarction (14.6% vs. 3.5%, P = 0.003), and increased rates of in-hospital major adverse cardiovascular events (MACE) (17.1% vs. 5.3%, P = 0.007).ConclusionsSBO is a clinically impactful yet partially preventable event in LAD bifurcation PCI. Key contributors include anatomical complexity, suboptimal protection strategies, and underutilization of intracoronary imaging. The V-RESOLVE score proved to be a robust predictor and may serve as a valuable tool for pre-procedural risk stratification, facilitating more tailored and effective intervention strategies.